National Syndicalism, Corporativism and ‘Hispanidad’. The appropriations of the Spanish Falange by Tacuara (1957-1973) (Quinto Sol, 2022)
The Movimiento Nacionalista Tacuara was the most relevant organisation of the nationalist right in the 1960s in Argentina. Its members defended radical nationalism and developed an anti-leftist and anti-Semitic repertoire of action. In addition, they formed a hybrid ideological corpus, which fused local elements with others from Europe. Interwar fascisms were fundamental in this process.In this paper, I address the appropriations of Falangism made by the Tacuara activism. In general, the existing studies about Tacuara recognize the centrality of Falangism, corporatism and the notions of ‘National Syndicalist State’ and ‘hispanidad’. However, the appropriations they made of these elements and the way in which they were re-signified in the light of local contexts have not yet been tackled.To shed light on the circulation of ideas between Argentina and Spain, I adopt a transnational perspective. I use as sources various Tacuara and Guardia Restauradora Nacionalista bulletins, reports produced by the intelligence services of the province of Buenos Aires, and oral history interviews conducted with former activists.
Keywords: Tacuara; nationalist right; Spanish Falange; national-syndicalism